Hepatitis G virus infection in chronic liver disease. Issue 1 (1st January 1998) - Guilera, M; Sáiz, J C; López-Labrador, F X; Olmedo, E; Ampurdanés, S; Forns, X; Bruix, J; Parés, A; Sánchez-Tapias, J M; de Anta, M T Jiménez; Rodés, J
Abstract : Background —The hepatitis G virus (HGV), a recently identified member of the Flaviviridae family, can cause chronic infection in man but the role of this agent in chronic liver disease is poorly understood. Aims —To evaluate the prevalence and meaning of HGV infection in a large series of patients with chronic liver disease. Subjects —Two hundred volunteer blood donors, 179 patients with chronic hepatitis C, 111 with chronic hepatitis B, 104 with alcoholic liver disease, 136 with hepatocellular carcinoma, and 24 with cryptogenic chronic liver disease were studied. Methods —HGV RNA was investigated in serum samples by reverse transcription and polymerase chain reaction amplification of the 5′ non-coding region of HCV and hybridisation to a specific probe. The main features of HGV RNA seropositive and seronegative patients were compared. Results —The prevalence of HGV infection was 3% in blood donors, 7% in chronic hepatitis C, 8% in chronic hepatitis B, 2% in alcoholic liver disease, 4% in hepatocellular carcinoma, and 8% in cryptogenic chronic liver disease. HGV infected patients tended to be younger than non-infected patients but no differences concerning sex, possible source of infection, clinical manifestations, biochemical and virological parameters, or severity of liver lesions were found. Conclusions —The prevalence of HGV infection in chronic liver disease seems to be relatively low in our area. Infection with HGV does not seem to play a significant pathogenic role in patients with chronic liver disease related to chronic HBV or HCV infection or to increased alcohol consumption, or in those with cryptogenic chronic liver disease.